Paraoxonase-1 gene in patients with chronic obstructive pulmonary disease investigation Q192R and L55M polymorphisms - Gurbuz, Sukru; Yildiz, Mustafa; Kara, Murat; Kargun, Kursat; Gurger, Mehtap; Atescelik, Metin; Alatas, Omer Dogan (Zhejiang Univ Sch Medicine, 2015)
BACKGROUND: The effect of increased oxidative stress on the development of chronic obstructive pulmonary disease (COPD) is well known. One of the antioxidative systems against oxidative stress in human body is paraoxonase (PON) enzyme that protects low density lipoproteins (LDL) against oxidation. This study aimed to explore the polymorphisms on PON1, Q192R, L55M genes of patients with COPD. METHODS: DNAs extraction was obtained from blood samples of 50 patients diagnosed with COPD and 50 patients as a control group who were presented to emergency clinic. Genotypes were obtained with polymerase chain reaction (PCR) and AIw I and Hsp92II restriction enzymes were used for Q192R and L55M polymorphisms, respectively. Analysis of data was done with the Chi-square test and Fisher's exact test. RESULTS: A statistically significant difference in Q192R polymorphism was found between the COPD patients and the control group (P=0.05). There was no statistically significant difference in L55M polymorphisms between the patient and control groups (P>0.05). Q192R polymorphism was significantly correlated with the PON1 gene and cigarette smoking; however other risk factors did not show any significant correlation with this polymorphism. Though L55M polymorphism was significantly correlated with family history and tuberculosis, there was no significant correlation with other risk factors. CONCLUSION: We believe that more studies are needed to study the correlation of L55M polymorphism with other factors.
Keywords: Chronic obstructive pulmonary disease; Paraoxonase; Polymorphism; Acute attack